Spindle cell sarcoma of sphenoid bone - Nimmagadda, Moorthy N. L.; Rao, Vithaleswar M.; S., Padmaja; Reddy, Harshini (International Journal of Research in Medical Sciences, 2017)
Primary bone tumors involving skull are extremely rare and they constitute 0.8% of all bone tumors. The common tumors that are seen in skull base include fibrous dysplasia, giant cell tumor, chordoma, ossifying fibroma, angiosarcoma. We report a rare case of spindle cell sarcoma arising from right sphenoid bone in a 70-year-old male which presented as unilateral defective vision with mild proptosis.